Pengaruh Financial Distress dan Persistensi Laba Terhadap Konservatisme Akuntansi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019-2021 - Dewi Rahayu; Junaidi Junaidi; Siti Aminah Anwar (Universitas Islam Malang, 2023)
This look at objectives to decide the impact of economic distress and profits sustainability, economic difficulties, profits permanence on accounting conservatism. This take a look at became carried out on manufacturing companies listed on the Indonesian stock exchange for the duration 2019-2021, the use of a targeted sampling method with a studies sample of forty companies. The analytical approach used is a partial test (t). The results of this study indicate that the effect of Financial Distress (X1), Profit Persistence, (X2) simultaneously affects Accounting Conservatism (Y) in manufacturing companies, Financial Distress (X1), has no effect on Accounting Conservatism (Y) in manufacturing companies, Profit Persistence, (X2), has a negative effect on Accounting Conservatism (Y) in manufacturing companies.Keywords: Financial distress, profit persistence, accounting conservatism